2010
DOI: 10.1007/s10620-010-1237-y
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Infection but Not Egg Antigen Promotes Recovery from Colitis in Outbred NMRI Mice

Abstract: The results presented here suggest that SEA treatment could not protect mice from acute colitis. However, both infection with S. mansoni and injection of SEA affect mucosal immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Schistosome egg induction of anti-inflammatory responses is essential in reducing hepatic inflammation and is key for host survival (22)(23)(24)(25)(26)(27). Similar to schistosome eggs, the saline homogenate of schistosome eggs, soluble egg antigen (SEA), also induces strong CD4 ϩ Th2 responses (15,22,23,(28)(29)(30)(31). In this regard, coadministration of SEA with a third-party protein antigen led to an increase in vaccine-specific Th2-type responses (32).…”
mentioning
confidence: 99%
“…Schistosome egg induction of anti-inflammatory responses is essential in reducing hepatic inflammation and is key for host survival (22)(23)(24)(25)(26)(27). Similar to schistosome eggs, the saline homogenate of schistosome eggs, soluble egg antigen (SEA), also induces strong CD4 ϩ Th2 responses (15,22,23,(28)(29)(30)(31). In this regard, coadministration of SEA with a third-party protein antigen led to an increase in vaccine-specific Th2-type responses (32).…”
mentioning
confidence: 99%
“…The majority have shown therapeutic effects on experimental autoimmunity or allergy. Some investigators reported that viable parasites were superior to administration of the antigens of parasites (Hunter et al, 2010;Bodammer et al, 2011;Osada et al, 2010) in therapeutic efficacy. In addition, there is still considerable controversy over the roles of regulatory cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Schistosoma spp.) have anti-colitic effects (Moreels et al, 2004;Ruyssers et al, 2009;Elliott et al, 2003;Mo et al, 2007;Zhao et al, 2009;Bodammer et al, 2011;Smith et al, 2007). A down-regulation of Th1/Th17-related cytokines and upregulation of anti-inflammatory cytokines are observed in most studies.…”
Section: Experimental Colitis As a Model Of Ibdmentioning
confidence: 99%
“…One method to overcome helminth-induced vaccine suppression is to identify vaccine vectors that are capable of producing vaccine-specific responses irrespective of helminth infection. In this regard, a Listeria vector HIV vaccine was recently shown to induce potent CD8 ϩ and Th1-type vaccine responses in schistosome-infected mice (12, 13).Schistosome soluble egg antigens (SEA) are potent inducers of CD4 ϩ Th2-type biasing (4,6,9,21), and in a previous study, we demonstrated that SEA coadministered with a third-party antigen was sufficient to induce vaccine-specific Th2-type cytokine responses (9). Here, we evaluated the influence of SEA on the ability of a Listeria vector HIV-1 vaccine to drive Th1-type and CTL responses in Th1-type C57BL/6 mice.…”
mentioning
confidence: 99%
“…Schistosome soluble egg antigens (SEA) are potent inducers of CD4 ϩ Th2-type biasing (4,6,9,21), and in a previous study, we demonstrated that SEA coadministered with a third-party antigen was sufficient to induce vaccine-specific Th2-type cytokine responses (9). Here, we evaluated the influence of SEA on the ability of a Listeria vector HIV-1 vaccine to drive Th1-type and CTL responses in Th1-type C57BL/6 mice.…”
mentioning
confidence: 99%